1997
DOI: 10.1007/s001250050739
|View full text |Cite
|
Sign up to set email alerts
|

24-h blood pressure and autonomic function is related to albumin excretion within the normoalbuminuric range in IDDM patients

Abstract: Summary Significant changes in both blood pressure, autonomic function and kidney ultrastructure are observed in insulin-dependent diabetic (IDDM) patients with microalbuminuria. Intervention strategies are evaluated at even earlier stages of disease. Identification of patients at risk of developing microalbuminuria must be based on a thorough knowledge of the relations between key pathophysiological parameters in patients with normoalbuminuria. The aim of the present study was to characterize the interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 36 publications
(60 reference statements)
8
67
0
5
Order By: Relevance
“…29 However, when both methods were entered in the same model, HBP lost its significance and nighttime ABP was the only independent predictor of worsening albuminuria. 29 Previous studies in diabetics 30,31 and nondiabetics 22 have shown that nighttime ABP gives the strongest correlations with albuminuria. This was not confirmed in this study, yet the findings do support the view that ABP is superior to clinical and also to home measurements in predicting albuminuria in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…29 However, when both methods were entered in the same model, HBP lost its significance and nighttime ABP was the only independent predictor of worsening albuminuria. 29 Previous studies in diabetics 30,31 and nondiabetics 22 have shown that nighttime ABP gives the strongest correlations with albuminuria. This was not confirmed in this study, yet the findings do support the view that ABP is superior to clinical and also to home measurements in predicting albuminuria in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous previous studies have established the superiority of 24 h AMBP over conventional office BP measurement for the association with [1,5,15,32,33] and prediction of hypertensive end-organ damage in diabetes [9,34,35]. Moran et al found that office and 24 h systolic AMBP were independently associated with albuminuria in elderly type 2 diabetic patients [4]; however in the longitudinal study mentioned above [9], ambulatory PP predicted progression of albuminuria above and beyond office BP.…”
Section: Discussionmentioning
confidence: 98%
“…14,18 A lot of evidence has been gathered that points to a strong link between nondipping phenomenon and autonomic neuropathy, even with a suggestion of a pathogenetic meaning, 13,[15][16][17]29 though some uncertainty still exists about all the pathogenetic mechanisms involved. Nevertheless, recently in 61 type I diabetic subjects, Stella et al 30 did not find any independent relationship between autonomic neuropathy and nondipping and suggested again a primary link between nondipping and diabetic nephropathy regardless of autonomic neuropathy but modified by low-density lipoprotein cholesterol and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Although some uncertainty still persists about the whole pathophysiology of the nondipping phenomenon, a series of studies have allowed to show the main pertinence of nondipping to diabetic autonomic neuropathy. [13][14][15][16][17][18] Notwithstanding, the predictive value of nondipping with regard to the presence of autonomic neuropathy has not been established.…”
Section: Introductionmentioning
confidence: 99%